Genetic Diversity of Elite and Exotic Oilseed Meadowfoam Germplasm using AFLP Markers - Sureeporn Katengam; Steven J. Knapp (Agriculture and Natural Resources, 2005)
Amplified fragment length polymorphism (AFLP) is a PCR-based marker, which is suitable for DNA fingerprinting. The AFLP fingerprinting has not been described in meadowfoam. This powerful method was utilized to access genetic diversity of 41 meadowfoam accessions belonging to the genus Limnanthes. The objectives were to estimate polymorphic information contents (PIC) for AFLP markers and genetic distance among germplasm, and to assess the pattern of genetic diversity in meadowfoam germplasm. One hundred and seventy six polymorphic AFLP markers were produced using 6 primer combinations across 41 accessions. The PIC value ranged from 0.0 to 0.5 and 42 % of germplasm showed high PIC scores in a range between 0.45 and 0.5. Genetic distance ranged from 0.14 to 0.55 with an average of 0.44. The UPGMA clustering phenogram based on the distance matrix was consistent with the known taxonomic classification. The first three principal coordinate analyses accounted for 37 % of total variation of genetic distance estimated. Cluster analysis and principal component analysis clearly separated L. floccosa from L. alba. Within L. alba, subspecies alba and versicolor were distinctly separated into two groups. The results suggested genetic diversity among meadowfoam germplasm was very high. This information is useful to layout framework for meadowfoam improvement thereby enhancing productivity and performance of cultivated meadowfoam.